Penelitian untuk Menekan Bullwhip Effect dalam Manajemen Rantai Pasok dengan Metode Periodic Review - Susriyati; Mohammad Farid; Beni Harma; Pebi Egia Sapitri (Universitas Putra Indonesia YPTK Padang, 2022)
This article presents research in the field of Supply Chain Management, the method used is descriptive exploratory method, using this research method it will be known about the object under study, resulting in conclusions from the research process carried out. The descriptive method is to find out and explain the characteristics of the variables studied in a situation and to describe aspects that are relevant to the research phenomenon. Research was conducted on this furniture business (CV. Budi Perabot), it is difficult for the company to determine the optimal amount of production because the demands of each retailer are different every month. After calculating the Bullwhip Effect using the Periodic Review method, it is known that the value of the Bullwhip Effect is a wardrobe of 1, a bed of 0.919, a dresser of 1.19, a display cabinet of 0.97. The application of the Periodic Review method has a positive impact because it is able to reduce or reduce the value of the Bullwhip Effect and minimize those in orders, demands and sales. In addition, the Periodic Review method is also able to create inventory at the recommended level on the number of orders. Comparison of the value of the Bullwhip Effect before applying the Periodic Review method for all products was 8,988 and after applying the Periodic Review method, it was reduced to 4,079. The comparison value was 4,909 after adding up all the products under study.